2014
DOI: 10.1016/j.amjsurg.2013.09.034
|View full text |Cite
|
Sign up to set email alerts
|

Small bowel obstruction in the virgin abdomen: the need for a mandatory laparotomy explored

Abstract: Adhesions are by far the most likely cause of SBO in patients without previous abdominal surgery followed by a small number of newly diagnosed malignancies. Both prevalences are in equal proportion to patients with previous abdominal surgery. A trial of nonoperative management may therefore be justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
87
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(90 citation statements)
references
References 18 publications
(35 reference statements)
0
87
2
1
Order By: Relevance
“…While the diagnosis of complete versus incomplete SBO has traditionally stemmed from clinical examination and plain film radiography, this has been aided by CT in recent years. Our study showed a 76% accuracy of CT diagnosis for the underlying aetiology, compared with earlier studies reporting between 27% and 53% . Besides helping to elucidate the aetiology of SBO, improved CT resolution also aids in assessing the extent of obstruction and complications such as strangulation, ischaemia and pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…While the diagnosis of complete versus incomplete SBO has traditionally stemmed from clinical examination and plain film radiography, this has been aided by CT in recent years. Our study showed a 76% accuracy of CT diagnosis for the underlying aetiology, compared with earlier studies reporting between 27% and 53% . Besides helping to elucidate the aetiology of SBO, improved CT resolution also aids in assessing the extent of obstruction and complications such as strangulation, ischaemia and pneumoperitoneum.…”
Section: Discussionmentioning
confidence: 39%
“…As SBO is classically presumed to be unlikely due to adhesions in patients without a prior abdominal surgery, many centres routinely advocate emergent operative management, although there is little evidence to support such indiscriminate practice . Taking into account contemporary studies that show a rising incidence of adhesions causing SBO, there is likely a role for non‐operative management in these patients as they can potentially be treated successfully with bowel decompression and serial assessment …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Una laparotomía temprana evitará serias complicaciones. Una conducta de "mirar para ver" (look and see), ante la sospecha de una HI, siempre será preferible a una de "esperar para ver" (wait and see) (53).…”
Section: Conclusiónunclassified
“…A few reports have been published on the etiology of BO without HL in adults, [2][3][4] but, to our knowledge, there has been no report on BO without HL in children. Therefore the detailed etiology and the appropriate interval to avoid resecting strangulated bowel in BO without HL in children remains unknown.…”
mentioning
confidence: 99%